2014
DOI: 10.1186/1471-2407-14-744
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative peripheral blood monocyte count predicts poor prognosis for hepatocellular carcinoma after curative resection

Abstract: BackgroundPeripheral blood monocyte count is an easily assessable parameter of systemic inflammatory response. The aim of this study was to determine whether monocyte count was prognostic in hepatocellular carcinoma (HCC) following hepatic resection.MethodsWe retrospectively reviewed 351 patients with HCC treated with hepatic resection from 2006 to 2009. Preoperative absolute peripheral monocyte count, demographics, and clinical and pathological data were analyzed.ResultsOn univariate and multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Owing to the producible, convenient, and inexpensive nature of circulating inflammation markers, great interests have been generated in elucidating their role in predicating cancer recurrence and death. Until now, the association between high peripheral blood monocytes and inferior survival has been proven in various malignancies, such as hepatocellular carcinoma, oral cavity cancer, oropharyngeal cancer, and lung cancer, as we have mentioned before . Our study evaluated the prognostic significance of peripheral blood monocytes in patients with ESCC who underwent esophagectomy.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Owing to the producible, convenient, and inexpensive nature of circulating inflammation markers, great interests have been generated in elucidating their role in predicating cancer recurrence and death. Until now, the association between high peripheral blood monocytes and inferior survival has been proven in various malignancies, such as hepatocellular carcinoma, oral cavity cancer, oropharyngeal cancer, and lung cancer, as we have mentioned before . Our study evaluated the prognostic significance of peripheral blood monocytes in patients with ESCC who underwent esophagectomy.…”
Section: Discussionmentioning
confidence: 85%
“…13 Recently, the pretreatments peripheral blood monocyte count and monocyte ratio have also been shown to be a convenient and inexpensive prognostic factor in various solid tumors, including hepatocellular carcinoma, oral cavity cancer, oropharyngeal cancer, and lung cancer. [14][15][16][17] These results indicate that peripheral blood monocytes are associated with a pro-inflammatory immune response in a tumor-promoting direction and promote tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous studies have shown that monocytes primarily mediate a robust innate immune response to systemic infection, and the recruitment of monocytes is a feature of the inflammatory response to infection [11,12]. Clinical studies also provided clues about the relationship between monocytes and viral pathogenesis, elevated preoperative monocyte count being an independent predictor of worse prognosis for patients with HCC after hepatic resection, especially for those with an HBV infection [27]. Clinical studies also provided clues about the relationship between monocytes and viral pathogenesis, elevated preoperative monocyte count being an independent predictor of worse prognosis for patients with HCC after hepatic resection, especially for those with an HBV infection [27].…”
Section: Discussionmentioning
confidence: 99%